"A prospective study on the clinical course and proposed morphological classification scheme of microsporidial keratoconjunctivitis.". (17th November 2021) - Mohanty, Amrita; Mitra, Sanchita; Das, Sujata; Priyadarshini, Smrutirekha; Sahu, Srikant K
ABSTRACT: Background and objective : To describe the clinical course and propose a morphological classification scheme of microsporidial keratoconjunctivitis. Methods : This is a prospective study at L V Prasad Eye Institute, Odisha, between August–January (2017–19). Patients of any age or sex, microbiologically proven as microsporidial keratoconjunctivitis were included. Demographic parameters, history, clinical course, and visual outcome were analysed. All received artificial tear substitutes till resolution and topical immunosuppressants used in cases of persisting sub-epithelial infiltrates (SEI) beyond 2 weeks. Results : Fifty-three eyes of 47 cases were included with males, 72.3%. Corneal lesions were classified into 3 morphological types- coarse, ring, and flat-topped (Type1, 2 & 3). Depending upon the location, Type 1 was further sub-divided into peripheral, paracentral, central, and diffuse (Type 1a, b, c & d). The mean age was highest in Type 3( p = .026). Risk factors and prior steroid use were most common in Type 1d. The mean duration of symptom before presentation was longest in Type 3(11.6 ± 3.65) days. Severe conjunctival congestion at presentation in more than half of the eyes were seen in Type 1a, 1b and 1d, with moderate congestion at Day14 persisting in 66.7% and 40% of eyes belonging to Type 1c and 1d, respectively. Keratic precipitates were most common in Type 2. The mean duration of resolution was longest in Type 1d (38 ± 15.87) days and shortest in type 1b (7.88 ± 2.47) days ( p = .022). Persistent SEIs beyond Day 90 were seen in total of 6 (11.3%) (Type 1c & 1d- 3 each) eyes and recurrent SEIs in 7(13.2%) (Type 1c-2 & 1d- 5) eyes. The mean duration of topical steroids use was longest in Type 1d (49.3 ± 22.3) days, followed by Type 1c (28 ± 0) days. Conclusion : Microsporidial keratoconjunctivitis can have a variable clinical presentation, the course of each being different depending on the host and ocular surface factors. Though considered as a self-limiting disease, central and diffuse coarse variety (Type1c&1d) required long-term topical immunosuppressants and follow-up.